FAKTOR-FAKTOR YANG MEMPENGARUHI WISATAWAN DALAM MEMILIH HOTEL BUDGET DI KOTA BANDUNG - Nandina Restu Febriana; Ersy Ervina (JURNAL ILMIAH EDUNOMIKA, 2023)
Bandung city is a preferred destination for both local and international tourists, who have diverse preferences influencing their choices. Therefore, a research study is necessary to analyze the factors influencing tourists' decisions in selecting budget hotels in Bandung. This study employs a quantitative approach with a survey and factor analysis to examine the factors influencing tourists' decisions in choosing budget hotels in Bandung. Data was collected through the distribution of questionnaires to tourists who have stayed in budget hotels in Bandung. The independent variables observed in this study are price, location, facilities, service, and promotion, while the dependent variable is the decision to choose a budget hotel. The results indicate that all independent variables significantly influence the decision to select budget hotels in Bandung. Price emerges as the most dominant factor, followed by location, facilities, service, and promotion. The conclusion of this research is that both local and international tourists visiting budget hotels in Bandung are primarily influenced by the factor of price.